EDUCATION FOR CITIZENS OF THE WORLD WITH AFRICAN DESCENDANT IDENTITY: CASE EDUCATIONAL INSTITUTION ANTONIA SANTOS, CARTAGENA DE INDIAS, COLOMBIA - Lago de Zota, Alejandrina; Lago de Fernández, Carmen; Lago de Vergara, Diana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
Colombia, a pluriethnic and multicultural nation, takes on ethnical education as a challenge and bets to autonomy, equity, and pertinence. The intercultural education constitutes a fundamental approach to build the peace and civic coexistence.From this standpoint, the research group RUECA from the Universidad de Cartagena (University of Cartagena) – Colombia, is committed with proposals for the curriculum which makes possible an intercultural education, with an afro-descendant identity for the citizens of the world, did a qualitative research with an ethnography approach.Data was gathered by means of observation, interviews, pedagogical approaches in the PEI and scholar papers, these showed a lacking in universal pedagogical thinking comprehension and in the symbology in family and community like an interpretative and reproductive reference of a culture.